2011
DOI: 10.1128/iai.01252-10
|View full text |Cite
|
Sign up to set email alerts
|

Serine Proteases Degrade Airway Mucins in Cystic Fibrosis

Abstract: Airway mucins are the major molecular constituents of mucus. Mucus forms the first barrier to invading organisms in the airways and is an important defense mechanism of the lung. We confirm that mucin concentrations are significantly decreased in airway secretions of subjects with cystic fibrosis (CF) who have chronic Pseudomonas aeruginosa infection. In sputum from CF subjects without a history of P. aeruginosa, we found no significant difference in the mucin concentration compared to mucus from normal contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 46 publications
6
47
0
Order By: Relevance
“…This ability also explained why the growth rate of the clinical strain was found to be the greatest on the mucin-supplemented SCFM medium where the growth also peaked earlier than in other cultures (Fig 1A and 1B). It has been suggested that serine proteases, elastase-like in particular, are responsible for mucin digestion in the cystic fibrosis lungs [71]. In our study, elastase-like activity was mainly detected in the culture supernatant of the clinical isolate (Fig 3), which may also contribute to mucin degradation [71].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This ability also explained why the growth rate of the clinical strain was found to be the greatest on the mucin-supplemented SCFM medium where the growth also peaked earlier than in other cultures (Fig 1A and 1B). It has been suggested that serine proteases, elastase-like in particular, are responsible for mucin digestion in the cystic fibrosis lungs [71]. In our study, elastase-like activity was mainly detected in the culture supernatant of the clinical isolate (Fig 3), which may also contribute to mucin degradation [71].…”
Section: Discussionsupporting
confidence: 50%
“…It has been suggested that serine proteases, elastase-like in particular, are responsible for mucin digestion in the cystic fibrosis lungs [71]. In our study, elastase-like activity was mainly detected in the culture supernatant of the clinical isolate (Fig 3), which may also contribute to mucin degradation [71]. Indeed, serine proteases were the dominant protease class secreted by the clinical strain (Fig 2).…”
Section: Discussionmentioning
confidence: 52%
“…One possibility is that other properties of cystic fibrosis mucus could override the feedback system. These include the presence of DNA (41), a different ratio of two mucin subtypes that make up the airway mucus (Muc5AC and Muc5B) as a result of goblet cell hyperplasia (42), and proteolytic cleavage of mucins by bacterial- and neutrophil-released proteases (43). Furthermore, the mucins themselves on the airway epithelia of cystic fibrosis patients may be abnormal, reflecting possible defects in mucin biosynthesis (3, 44) or defective unfolding during release from intracellular granules as a result of defective CFTR-mediated HCO 3 − transport (4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa is the most prevalent infectious agent in this population and is associated with lung function decline. CF patients also suffer from sustained airway neutrophilia [156], resulting in an excess of purulent phlegm and pro-inflammatory factors [157]. The combination of infection and inflammation ultimately drives >80% of CF patients’ morbidity and mortality [155].…”
Section: Clinical and In Vivo Research On The Health Effects Of Scn−mentioning
confidence: 99%